Effect of serve execution on serve efficacy in men's and women's beach volleyball - Lopez-Martinez, A. B.; Palao, J. M. (International Journal of Applied Sports Sciences, 2009)
The purpose of this study was to assess the effect of serve technique and its manner of execution on the efficacy of the serve in beach volleyball according to gender. A total of 1073 serves from 25 sets of the 2003 World Championship and the 2004 Olympic Games were analyzed (508 serves from men's games and 576 serves from women's games). The variables studied were: type of serve (standing serve or jump serve), manner of execution (origin, destination, and distance), serve efficacy, result of the action, and gender. Descriptive and inferential analyses of the data were done (chi-square test and likelihood ratio) with a level of statistical significance set at p<0.05. The results show that for both genders: a) the jump serve involved a higher number of errors, points, and actions that limited the opponent; b) the jump serve and standing serve involved similar levels of efficacy; c) the serve directed toward the interference zone between receivers was the most effective; d) players used the jump serve and the standing serve; and e) no relationship was found between type of serve and result of the rally.